Suppose $A=(a_{ij})$ is a $n×n$ matrix by $a_{ij}=\sqrt{i^2+j^2}$. I have tried to check its sign by matlab. l find that the determinant is positive when n is odd and negative when n is even. How to prove it?

  • 3
    $\begingroup$ Notice that A is symmetric, so has an orthogonal eigenbasis with real eigenvalues (of which determinant is the product). $\endgroup$
    – lisyarus
    Commented Nov 14, 2020 at 7:26
  • 3
    $\begingroup$ Sure looks like $A$ has a single positive eigenvalue $>(n-1/2)^2$ and the remaining eigenvalues are all negative. This would imply your claim, but is probably equally tough to prove. It is not really surprising that some of those negative eigenvalues are tiny. After all, the bottom rows (or the rightmost columns) are nearly parallel. Anyway, I don't have any kind of intuition about how this might be settled. $\endgroup$ Commented Nov 14, 2020 at 7:46
  • 2
    $\begingroup$ It would be simple without the square roots :-) $\endgroup$ Commented Nov 14, 2020 at 7:58
  • 2
    $\begingroup$ Let $B = (b_{ij})$ be an $n \times n$ matrix with $b_{ij} = i+j$ (which clearly has rank $2$). From playing around in MATLAB, I conjecture $B-A$ is positive definite. If true, this would imply that $A$ has at most two non-negative eigenvalues. I still don't know how to prove this conjecture, but it might be helpful to those trying to solve this problem. $\endgroup$
    – JimmyK4542
    Commented Nov 14, 2020 at 9:41
  • 9
    $\begingroup$ This already had an answer in 2013: math.stackexchange.com/questions/599644/… $\endgroup$ Commented Dec 20, 2020 at 7:02

3 Answers 3


Recall that $e^{-|x|}=\int_0^\infty e^{-sx^2}\,d\mu(s)$ for some non-negative probability measure $\mu$ on $[0,+\infty)$ (Bernstein, totally monotone functions, etc.). Thus $e^{-t|x|}=\int_0^\infty e^{-st^2x^2}\,d\mu(s)$. for $t>0$. In particular, since $(e^{-st^2(i^2+j^2)})_{i,j}$ are rank one non-negative matrices, their mixture $(e^{-t\sqrt{i^2+j^2}})_{i,j}$ is a non-negative matrix for all $t>0$. Hence, considering the first two terms in the Taylor expansion as $t\to 0+$, we conclude that $-A$ is non-negative definite on the $n-1$-dimensional subspace $\sum_i x_i=0$, so the signature of $A$ is $1,n-1$. To finish, we just need to exclude the zero eigenvalue, i.e., to show that the columns are linearly independent, which I leave to someone else (i.e., up to this point we have shown that the determinant has the conjectured sign or is $0$).

  • 3
    $\begingroup$ Wow, I wish I understood this argument. Can you elaborate more on the existence of the measure $\mu$? $\endgroup$ Commented Dec 18, 2020 at 21:09
  • 3
    $\begingroup$ @QiaochuYuan Look at djalil.chafai.net/blog/2013/03/23/… $\endgroup$
    – fedja
    Commented Dec 18, 2020 at 21:11
  • 1
    $\begingroup$ Amazing, I wish I can come up with this answer myself. $\endgroup$ Commented Dec 18, 2020 at 21:15
  • 1
    $\begingroup$ Wow! What is the mixture of a matrix? And why the space of zero sum coordinates pops up? I would love to see a more detailed answer :) $\endgroup$ Commented Dec 18, 2020 at 21:48
  • 2
    $\begingroup$ Could you expand this answer a bit for simpletons such as myself? $\endgroup$
    – Alexander Gruber
    Commented Dec 18, 2020 at 22:51

What follows is just an explication of fedja's beautiful ideas, with the minor gap of non-zero-ness filled in. There seemed like enough interest to warrant sharing it. Along the way I decided to make it very explicit to make it more accessible, since it's so pretty.

Let $$A = \left(\sqrt{i^2+j^2}\right)_{1 \leq i, j \leq n}.$$

Theorem: $(-1)^{n-1} \det(A) > 0$.

Proof: Since $A$ is symmetric, it has an orthogonal basis of eigenvectors, and its determinant is the product of its eigenvalues. We'll show there are $n-1$ negative eigenvalues and $1$ positive eigenvalue, i.e. $A$ is non-degenerate with signature $(1, n-1)$.

Let $x_0 := (1, \ldots, 1)^\top$. Considering the quadratic form corresponding to $A$, $$x_0^\top A x_0 = \sum_{1 \leq i, j \leq n} \sqrt{i^2 + j^2} > 0.$$ Thus there must be at least $1$ positive eigenvalue $\lambda_+>0$. On the other hand, we have the following.

Claim: If $x \cdot x_0 = 0$ and $x \neq 0$, then $x^\top A x < 0$.

Assume the claim for the moment. If $A$ had another eigenvalue $\lambda \geq 0$, then the $2$-dimensional subspace $\mathrm{span}\{\lambda_0, \lambda\}$ would intersect the $(n-1)$-dimensional subspace $\{x : x \cdot x_0 = 0\}$ non-trivially, but at that point $y$ we would have both $y^\top A y \geq 0$ and $y^\top A y < 0$, a contradiction. So, the theorem follows from the claim. For readability, we break the argument into two pieces.

Subclaim: If $x \cdot x_0 = 0$ and $x \neq 0$, then $x^\top A x \leq 0$.

Proof of subclaim: We first introduce $$B(t) := \left(e^{-t\sqrt{i^2+j^2}}\right)_{1 \leq i,j \leq n}.$$ Intuitively, $A$ is the linear coefficient of the Taylor expansion of $B$ around $t=0$. More precisely, working coefficient-wise, $$\lim_{t \to 0} \frac{B_0 - B(t)}{t} = A$$ where $B_0 := B(0) = (1)_{1 \leq i, j \leq n}$ is the matrix of all $1$'s.

Since $x \cdot x_0 = 0$, we have $B_0 x = 0$. Thus $$\tag{1}\label{1}x^\top A x = \lim_{t \to 0} x^\top \frac{B_0 - B(t)}{t} x = -\lim_{t \to 0} \frac{x^\top B(t)\,x}{t}.$$

The key insight is to express the quadratic form $x^\top B(t) x$ in a manifestly positive way. For that, it is a fact1 that for all $z \geq 0$, $$e^{-\sqrt{z}} = \frac{1}{2\sqrt{\pi}} \int_0^\infty e^{-zs} s^{-3/2} \exp\left(-\frac{1}{4s}\right)\,ds.$$

Thus, for all $t \geq 0$, we have the following entry-wise equality: $$B(t) = \left(e^{-t\sqrt{i^2+j^2}}\right)_{1 \leq i,j \leq n} = \int_0^\infty \left(e^{-t^2(i^2+j^2)s}\right)_{1 \leq i,j \leq n} \, g(s)\,ds$$ where $$g(s) := \frac{1}{2\sqrt{\pi}} s^{-3/2} \exp\left(-\frac{1}{4s}\right) > 0\quad\text{for all }s > 0.$$ The integrand matrices can be decomposed as an outer product, namely $$\left(e^{-t^2(i^2+j^2)s}\right)_{1 \leq i,j \leq n} = \left(e^{-t^2 i^2 s} e^{-t^2 j^2 s}\right)_{1 \leq i,j \leq n} = u(s, t)u(s, t)^\top$$ where $$u(s, t) := (e^{-t^2 i^2 s})_{1 \leq i \leq n}$$ is a column vector. Thus, $$\begin{align*} x^\top B(t)\,x &= x^\top\left(\int_0^\infty u(s, t) u(s, t)^\top \, g(s)\,ds\right)x \\ &= \int_0^\infty (u(s, t)^\top x)^\top (u(s, t)^\top x)\,g(s)\,ds \\ &= \int_0^\infty (u(s, t) \cdot x)^2\,g(s)\,ds. \end{align*}$$ Hence \eqref{1} becomes $$\tag{2}\label{2}x^\top A\,x = -\lim_{t \to 0^+} \int_0^\infty \frac{(u(s, t) \cdot x)^2}{t} g(s)\,ds.$$

It is now clear that $x^\top A\,x \leq 0$ since $g(s) \geq 0$, finishing the subclaim.

Proof of claim: It will take a little more work to show that $x^\top A\,x < 0$ is strict. Let $t = 1/\alpha$ for $\alpha > 0$. Apply the substitution $s = \alpha^2 r$ to the integral in \eqref{2} to get $$\begin{align*} \int_0^\infty \frac{(u(s, t) \cdot x)^2}{t} g(s)\,ds &\geq \int_{\alpha^2/2}^{\alpha^2} \frac{(u(s, t) \cdot x)^2}{t} g(s)\,ds \\ &= \int_{1/2}^1 (u(\alpha^2 r, 1/\alpha) \cdot x)^2 \alpha g(\alpha^2 r)\,\alpha^2\,dr \\ &= \int_{1/2}^1 \alpha^3 (u(r, 1) \cdot x)^2 \frac{1}{2\sqrt{\pi}} \alpha^{-3} r^{-3/2} \exp\left(-\frac{1}{4\alpha^2 r}\right)\,dr \\ &= \frac{1}{2\sqrt{\pi}} \int_{1/2}^1 (u(r, 1) \cdot x)^2 r^{-3/2} \exp\left(-\frac{1}{4\alpha^2 r}\right)\,dr. \end{align*}$$

Thus \eqref{2} becomes $$\begin{align*} x^\top A\,x &\leq -\lim_{\alpha \to \infty} \frac{1}{2\sqrt{\pi}} \int_{1/2}^1 (u(r, 1) \cdot x)^2 r^{-3/2} \exp\left(-\frac{1}{4\alpha^2 r}\right)\,dr \\ &= -\frac{1}{2\sqrt{\pi}} \int_{1/2}^1 (u(r, 1) \cdot x)^2 r^{-3/2}\,dr. \end{align*}$$

Hence it suffices to show that $u(r, 1) \cdot x \neq 0$ for some $1/2 \leq r \leq 1$. Indeed, $\{u(r_j, 1)\}$ is a basis for any $r_1 < \cdots < r_n$. One way to see this is to note that the matrix is $\left(e^{-i^2 r_j}\right)_{1 \leq i, j \leq n} = \left(q_i^{r_j}\right)_{1 \leq i, j \leq n}$ where $q_i := e^{-i^2}$. Since $0 < q_n < \cdots < q_1$, this matrix is an (unsigned) exponential Vandermonde matrix in the terminology of Robbin--Salamon, and therefore has positive determinant. Hence $u(r, 1) \cdot x = 0$ for all $1/2 \leq r \leq 1$ implies $x=0$. contrary to our assumption. This completes the claim and proof. $\Box$

1As fedja points out, existence of an appropriate expression follows easily from Bernstein's theorem on completely monotone functions. As you'd expect, this explicit formula can be done by residue calculus.

  • 4
    $\begingroup$ This is lovely, thanks for writing this up! It’s a genuinely new technique for me to see someone analyzing a matrix by analyzing its pointwise exponential, will have to keep that in mind. $\endgroup$ Commented Dec 19, 2020 at 18:35
  • 3
    $\begingroup$ @QiaochuYuan Agreed, the idea seems very novel to me too. Even special cases give fun results, like when $n=2$ and $x = (1, -1)^\top$, it shows that $\sqrt{2} - 2\sqrt{5} + \sqrt{8} < 0$. Try finding another "conceptual" explanation for that! $\endgroup$ Commented Dec 20, 2020 at 8:15

The beautiful idea of @fedja: (also used by @Swanson:) is to show that $$\sum_{i,j} \sqrt{\lambda_i+\lambda_j}\, x_i x_j$$ is negative definite on the subspace $\sum x_i = 0$. Here is another way to check this. We have the integral formula

$$\sqrt{\lambda} = \frac{1}{2 \sqrt{\pi}} \int_{0}^{\infty}\frac{1 - e^{-\lambda s}}{s^{3/2}} ds$$ so we can write $$\sum \sqrt{\lambda_i+\lambda_j}\, x_i x_j = \frac{1}{2 \sqrt{\pi}}\int_{0}^{\infty} \frac{\sum_{i,j} (1- e^{-(\lambda_i+\lambda_j) s})x_i x_j} { s^{3/2}} d\,s $$ But now observe that since $\sum x_i = 0$ we also have $\sum_{i,j} x_i x_j=0$, so the numerator in the integral equals $$-\sum _{i,j} e^{-(\lambda_i+\lambda_j) s}x_i x_j= - (\sum_i e^{-\lambda_i s} x_i)^2 \le 0$$ so the integral is $\le 0$. But since the functions $(e^{-\lambda s})_{\lambda}$ are a linearly independent system, the integral is is fact $<0$ if not all the $x_i$ are $0$. Therefore, the quadratic form is negative definite on $\sum_i x_i = 0$

Now, using Cauchy interlacing theorem we conclude that the matrix $(\sqrt{\lambda_i+\lambda_j})$ has one positive eigenvalue and the rest negative. ( or: there is no $2$ subspace on which this form is $\ge 0$, since any such subspaces intersects $\sum x_i=0$ non-trivially).

This can be generalized, using other Bernstein functions, for instance $\lambda\mapsto \lambda^{\alpha}$ ($0<\alpha < 1$), since we have the integral representation $$\lambda^{\alpha} = \frac{\alpha}{\Gamma(1-\alpha)} \int_{0}^{\infty}\frac{1- e^{-\lambda s}}{s^{\alpha+1}} d s$$

One can take a look at the book of Schilling et al -- Bernstein functions theory and applications

Note: from numerical testing, it seems that matrices of form $((\lambda_i +\mu_j)^{\alpha})$ ($0<\alpha<1$, $\lambda_i$, $\mu_i$ positive and ordered in the same way), have one eigenvalue positive and the rest negative. It would imply that the matrix $(-(\lambda_i +\mu_j)^{\alpha})$ is totally negative.

$\bf{Added:}$ Sketch of proof for the integral representation:

For $\beta> 0$ we have $$\Gamma(\beta) = \int_{0}^{\infty} e^{-s} s^{\beta}\frac{d s}{s} = \int_{0}^{\infty}e^{-\lambda s} (\lambda s)^{\beta} \frac{d s}{s}= \lambda^{\beta} \int_{0}^{\infty}e^{-\lambda s} s^{\beta} \frac{d s}{s}$$ and so $$\lambda^{-\beta} = \frac{1}{\Gamma(\beta)} \int_0^{\infty} e^{-\lambda s} s^{\beta-1} d s$$ Now integrate wr to $\lambda$ from $0$ to $\lambda$ and get the formula for $1-\beta = \alpha>0$.

$\bf{Added:}$ Let's show that for $\alpha$ not an integer, $(\lambda_i)$, $(\mu_i)$ two $n$-uples of distinct positive numbers, the determinant $\det((\lambda_i + \mu_j)^{\alpha})_{ij}$ is $\ne 0$. Now, the determinant is $0$ is equivalent to its columns being linearly dependent, that is there exist $a_i$ not all zero such that the function $$\sum a_j (x+\mu_j)^{\alpha}$$ is zero at the points $x= \lambda_i$. Let us show by induction on $n$ that such a function $\sum_{j=1}^n a_j (x + \mu_j)^{\alpha}$ cannot have $n$ positive zeroes.

For $n=1$ it's clear. Assume the statement is true for $n-1$ and let's prove it for $n$.

Write $f(x) =\sum a_j (x + \mu_j)^{\alpha}$. We may assume (a shift in argument $x$) that the smallest $\mu_1 =0$. Now the positive zeroes of $f(x)$ are the positive zeroes of $$\frac{f(x)}{x^{\alpha}} = a_1 + \sum_{j>1} a_j (1 + \frac{\mu_j}{x})^{\alpha}=a_1 + \sum_{j>1} a_j \mu_j^{\alpha}\, (\frac{1}{\mu_j} + \frac{1}{x})^{\alpha} $$ So now we get another function $g(x) = a_1 + \sum b_j( x+ \xi_j)^{\alpha}$ that has $n$ positive roots, so its derivative will have $n-1$ positive roots. But the derivative is a sum of $n-1$ terms (involving the exponent $\alpha-1$). Now apply the induction hypothesis.

Note: with a bit more care, we show that the determinant $\det ((\lambda_i + \mu_j)^{\alpha})$ is $\ne 0$ whenever $(\lambda_i)$, $(\mu_i)$ are $n$-uples of distinct positive numbers and $\alpha\not = 0, 1, \ldots, n-2$. Its sign will depend only on $n$, $\alpha$ (perhaps the integral part of $\alpha$ ) ( and the ordering of the the $\lambda_i$, $\mu_i$).

An interesting problem is to determine this sign. We understand the case $0< \alpha<1$ (and $\alpha < 0$). Perhaps $\alpha \in (1,2)$ next? The determinant $\det((\lambda_i + \lambda_j)^{\alpha})$ should be negative if $n\ge 2$.

  • 1
    $\begingroup$ as far as putting an @username within an answer, we tested it, the indicated person does not get a notification of that reference. Works in comments mostly...I guess including the @ sign does make it clear that a username is intended, for later readers $\endgroup$
    – Will Jagy
    Commented Dec 19, 2020 at 17:57
  • $\begingroup$ @Will Jagy: Thanks for the heads up! $\endgroup$
    – orangeskid
    Commented Dec 19, 2020 at 18:12
  • $\begingroup$ Yes, in fact l have seem that there always exists $x$ such that $x^TAx<0$, but l can't understand how to use the Cauchy interlacing theorem. $\endgroup$
    – Jimmy
    Commented Dec 20, 2020 at 4:52
  • $\begingroup$ @Jimmy: Oh, you can think like this: consider the space spanned by the eigenvectors corresponding to the eigenvalues $\ge 0$. On this space we have $\langle A v, v\rangle \ge 0$ for all $v$. If this space had dimension $\ge 2$, it would intersect $\sum x_i=0$ in a non-zero vector, and you get a contradiction, since we also know $\langle A v, v\rangle <0$ as we showed. So at most $1$ eigenvalue $\ge 0$. Since the sum of eigenvalues is positive, there is exactly $1$. You can forget Cauchy for now, but it uses the argument above in fact, if you understand this, you can prove Cauchy on your own. $\endgroup$
    – orangeskid
    Commented Dec 20, 2020 at 5:38
  • $\begingroup$ l understand your thought, but for instance $P^{T}AP=diag{1,1,-1,\cdots,-1}$,then you let y=(1,-1,0,\cdots,0) in the supspace $\sum_{i=1}^nx_i=0$ and let $x=Py$, then $x^{T}Ax=y^{T}y>0$.However, you can't assure that $x$ is still in the supspace $\sum_{i=1}^nx_i=0$. $\endgroup$
    – Jimmy
    Commented Dec 21, 2020 at 2:24

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .